1978
DOI: 10.1021/ac50026a004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carotenoid and porphyrin pigments of geochemical interest by high-performance liquid chromatography

Abstract: High-performance liquid chromatography (HPLC) is shown to be a powerful tool in the analysis of carotenoid and porphyrin pigments. Columns packed with 5-µ irregular silica gel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…That is, methanol is known to deactivate chromatographic silica (see Purcell, 1958). Through comparing chromatographic mobility of the carotene-diols isolated from Leg 64 samples to those reported from other studies (e.g., see Fiksdahl et al, 1978;Hajibrahim et al, 1978) and to the known position of authentic chlorophyll-a on the system used herein with that reported by others (Fiksdahl et al, 1978), these compounds appear to be zeaxanthin-like (XXXII: jO,ß-carotene-3,3'-diol) and diatoxanthin-like (XXXIII: 7,8-didehydro-ß,/3-carotene-3,3'-diol) compounds. However, further study and mass spectrometric analyses are required before assigning definite structure.…”
Section: Apo-carotenoids Refers To Tentatively Identified Apo-carotenmentioning
confidence: 98%
See 1 more Smart Citation
“…That is, methanol is known to deactivate chromatographic silica (see Purcell, 1958). Through comparing chromatographic mobility of the carotene-diols isolated from Leg 64 samples to those reported from other studies (e.g., see Fiksdahl et al, 1978;Hajibrahim et al, 1978) and to the known position of authentic chlorophyll-a on the system used herein with that reported by others (Fiksdahl et al, 1978), these compounds appear to be zeaxanthin-like (XXXII: jO,ß-carotene-3,3'-diol) and diatoxanthin-like (XXXIII: 7,8-didehydro-ß,/3-carotene-3,3'-diol) compounds. However, further study and mass spectrometric analyses are required before assigning definite structure.…”
Section: Apo-carotenoids Refers To Tentatively Identified Apo-carotenmentioning
confidence: 98%
“…Re-equilibration of the column, following a 20% methanol in acetone flush, for periods of 20 to 30 minutes also enhanced separation of the hydrocarbon pigments (cf. Hajibrahim et al, 1978).…”
Section: Pigment Yield and Observed Trendsmentioning
confidence: 99%
“…Until recently, the complexity of these mixtures outstripped the techniques available for separation, precluding analysis of all but major pigments (Fox, 1937;Fox et al, 1945; Carotenoids characteristic of specific classes of organisms have now been used to identify sources of sedimentary organic matter Hajibrahim et al, 1978, Cardoso et al, 1978Griffiths et al, 1978), deduce transformation pathways (Repeta and Gagosian, 1982 a,b), recognize pollution events (Griffiths and Edmondson, 1975;Griffiths et al, 1969), and monitor eutrophication in Lake Zurich (Zullig, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports of HPLC separations of marine carotenoids (Stewart and Wheaton, 1971;Cadosch and Euguster 1974;Eskins et al, 1977;Fiksdahl et al, 1978;Hajibrahim et al, 1978;Vecchi and Muller, 1979;Ohmacht, 1979;Eskins and Dutton, 1979;Paankker and Gallegraeff, 1979;Ronneberg et al, 1980;Davies and Holdsworth 1980;Schiedt et al, 1981). Schwartz and Von Elbe (1982) have reviewed HPLC analysis of plant pigments, and systematic studies of a wide variety of carotenes and xanthophylls have been reported by Fiksdahl et al, (1978) and Matus et al, (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Normal phase HPLC was carried out based on a system reported by Hajibrahim et al (1978). Separations were made on a silica column (Partisil5 pm irregular) using a concave gradient (curve 7 on the Waters 720 programme) of acetone (2-75%) in hexane for 30 minutes at 1 ml/min.…”
Section: Analysis By Hplcmentioning
confidence: 99%